Low-cost high-temperature-resistant density-adjustable quartz fiber reinforced quartz-based composite material and preparation method thereof
Through the treatment of liquid borazane and the impregnation and sintering of silicon sol, the problems of long preparation cycle and high cost of quartz fiber-reinforced quartz matrix composites are solved, and quartz fiber-reinforced quartz with low cost, high density and excellent high temperature resistance are achieved. The matrix composite material meets the performance requirements of low dielectric radome or antenna window.
Patent Information
- Application Number
- CN202411794220.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing quartz fiber reinforced quartz matrix composite materials have a long preparation cycle, complex process and high cost, and limited high temperature performance, which cannot meet the performance requirements of low dielectric radome or antenna windows.
The quartz fiber three-dimensional fabric is treated with liquid boronazane to form a boron nitride coating, combined with silicon sol impregnation and sintering, to achieve high-density quartz fiber reinforced quartz matrix composite materials in one preparation process, simplifying the process and reducing costs.
The preparation of low-cost, high-temperature-resistant quartz fiber reinforced quartz matrix composite material is realized, with a density of 1.2-1.6g/cm3, meeting the requirements of low dielectric characteristics and excellent mechanical properties, simplifying the preparation cycle and reducing equipment requirements.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-temperature wave-transmitting materials, and in particular to a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material and a preparation method thereof. Background Art
[0002] Quartz fiber reinforced quartz matrix (SiO 2f / SiO2) composite materials are widely used in missile radomes or antenna windows due to their excellent wave transmission, load-bearing, heat-insulating and other properties. The mainstream preparation process of this material system adopts a sol-gel process to impregnate reinforced fabrics with silica sol for multiple times, and then solidify and sinter. At present, it is mainly developing towards high-density quartz fiber reinforced quartz-based composite materials.
[0003] High density SiO 2f / SiO2 composite materials require multiple (usually 3-9 times, or even more than 10 times) cycles to prepare, and the preparation cycle is long. 2f The application temperature range of / SiO2 composite materials is limited. After exceeding 1150°C, the quartz fiber quickly crystallizes and the mechanical properties drop sharply. Based on the above problems, ZL201810957466.9 discloses a high-temperature resistant quartz fiber reinforced silica-based composite material and its preparation method and application. The method first coats the quartz fiber to prepare a ceramicized fabric preform on the surface of the quartz fiber, and then the preform is treated with silica sol impregnation and drying for 5-9 times to obtain a SiO2 preform with a density of 1.70-1.85. 2f / SiO2 composite material. The coating preparation method of this method is complicated, the preparation cycle of quartz-based composite materials is long, and the cost is high. ZL202111175316.0 discloses a high-density fiber-reinforced quartz ceramic composite material and its preparation method. The method first uses amorphous silicon dioxide slurry to impregnate the three-dimensional fabric at least, dry and sinter it twice, and then impregnate the three-dimensional fabric with silica sol of different particle sizes, dry and sinter it twice to obtain a high-density fiber-reinforced quartz ceramic composite material. The density of this material is between 1.65-1.75. This method still requires multiple impregnations of preforms / rough blanks, a long preparation cycle, high cost, and no optimization and improvement of high-temperature performance.
[0004] Therefore, in view of the above problems, the present invention urgently needs to provide a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material and a preparation method thereof. The low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material preparation method is proposed to solve the technical problems of long preparation cycle, complex preparation process and high cost of quartz fiber reinforced quartz-based composite materials in the prior art.
[0006] The present invention provides a method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material, comprising the following steps: Quartz fiber three-dimensional fabric debonding treatment; The debinding treated quartz fiber three-dimensional fabric is immersed in liquid borazine, heated to 80-95° C. in an inert atmosphere, kept warm for 1-3.5 hours at a pressure of 0.2-1.0 MPa, and sintered at 800-900° C. to obtain a rough fabric; The rough fabric is impregnated in silica sol, heated and kept warm under vacuum, and after impregnation, the silica sol is removed, heated and kept warm under vacuum, and sintered to obtain a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material.
[0007] Preferably, the rough fabric is immersed in silica sol, the liquid level of silica sol is 1 / 2-2 / 3 of the height of the rough fabric, the temperature is raised to 55-65°C under vacuum, and the temperature is kept for 10 hours, the liquid level of silica sol is reduced to 1 / 10-1 / 2 of the height of the rough fabric, and the temperature is raised to 85-100°C and the temperature is kept for 10 hours; Remove the silica sol, first raise the temperature to 125-150°C and keep it for 10 hours, then raise the temperature to 200-220°C and keep it for 5 hours, sinter at 500-750°C and keep it for 1-3 hours, and obtain a low-cost, high-temperature resistant, density-adjustable quartz fiber reinforced quartz-based composite material.
[0008] Preferably, the amount of liquid borazine added is 20%-30% of the weight of the three-dimensional quartz fiber fabric.
[0009] Preferably, the mass concentration of the silica sol is 25-60%.
[0010] Preferably, the debinding process of quartz fiber three-dimensional fabric is as follows: The quartz fiber three-dimensional fabric is immersed in the impregnating agent for immersion treatment, and then dried; wherein the immersion pressure is 0.4-5 MPa, the immersion time is 12-24 hours; the drying temperature is 60-110° C., and the drying time is 1-3 hours; Preferably, the wetting agent includes any one or more of ethyl acetate, acetone or toluene.
[0011] Preferably, the inert atmosphere includes at least one of nitrogen and argon.
[0012] Preferably, the quartz fiber three-dimensional fabric is prepared by a needle-punching stitching process.
[0013] Preferably, the mass proportion of quartz fibers in the quartz fiber three-dimensional fabric is 35-45%.
[0014] The present invention also provides a low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material obtained based on the low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material preparation method as described in any one of the above.
[0015] The low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material preparation method provided by the present invention has the following improvements compared with the prior art: 1. The low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material preparation method provided by the present invention comprises the following steps: firstly treating a quartz fiber three-dimensional fabric with liquid borazine; since the liquid borazine has the characteristic of low viscosity, it can quickly impregnate and fill the gaps in the fiber bundles and between the fiber bundles of the three-dimensional fabric; and, due to the high activity and high ceramic rate of the liquid borazine, under the conditions of 80-95°C, 0.2-1.0MPa, and 1-3.5h, the borazine pinched in the gaps between the fiber bundles of the quartz fiber three-dimensional fabric can quickly foam into a solid state, and the fiber bundles of the quartz fiber three-dimensional fabric are filled with the liquid borazine. Due to the large number of quartz fibers and strong surface tension, the borazine between the fiber yarns is converted into a solid with relatively small pores. Under the protection of an inert atmosphere at 800-900°C, the solidified borazine is converted into a boron nitride ceramic, that is, a boron nitride coating is formed on the surface of the quartz fiber, which improves the antioxidant and high temperature resistance. The obtained fabric rough is impregnated in silica sol, and then solidified and sintered. The quartz fiber reinforced quartz-based composite material only needs to go through a one-time preparation process, and does not need to go through a cyclic densification process. Its density can reach 1.2-1.6g / cm 3 , meeting the use requirements of low dielectric antenna cover or antenna window for material performance, simple manufacturing process, short preparation cycle, excellent high temperature resistance, low cost and low equipment requirements.
[0016] 2. The present invention provides a method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material. During the impregnation process of the silica sol, the liquid level of the silica sol is lower than the rough fabric, forming a certain height difference. The silica sol can penetrate relatively evenly into the interior of the fabric through the boron nitride pores between the quartz fiber bundles. The impregnation state of the fabric gradually decreases as the temperature increases, and the silica sol can be further impregnated into the interior of the fabric through capillary force in the initial stage of curing, thereby finally achieving uniform and dense quartz fiber reinforced quartz-based composite materials. DETAILED DESCRIPTION
[0017] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The present invention provides a method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material, comprising the following steps: Quartz fiber three-dimensional fabric debonding treatment; The debinding treated quartz fiber three-dimensional fabric is immersed in liquid borazine, heated to 80-95° C. in an inert atmosphere, kept warm for 1-3.5 hours at a pressure of 0.2-1.0 MPa, and sintered at 800-900° C. to obtain a rough fabric; The rough fabric is impregnated in silica sol, heated and kept warm under vacuum, and after impregnation, the silica sol is removed, heated and kept warm under vacuum, and sintered to obtain a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material.
[0019] Specifically, the rough fabric is immersed in silica sol, the liquid level of silica sol is 1 / 2-2 / 3 of the height of the rough fabric, the temperature is raised to 55-65°C under vacuum, and the temperature is kept for 10 hours, the liquid level of silica sol is reduced to 1 / 10-1 / 2 of the height of the rough fabric, and the temperature is raised to 85-100°C and the temperature is kept for 10 hours; Remove the silica sol, first raise the temperature to 125-150°C and keep it for 10 hours, then raise the temperature to 200-220°C and keep it for 5 hours, sinter at 500-750°C and keep it for 1-3 hours, and obtain a low-cost, high-temperature resistant, density-adjustable quartz fiber reinforced quartz-based composite material.
[0020] Specifically, the amount of liquid borazine added is 20%-30% of the weight of the quartz fiber three-dimensional fabric.
[0021] Specifically, the mass concentration of the silica sol is 25-60%.
[0022] Specifically, the debonding process of quartz fiber three-dimensional fabric is as follows: The quartz fiber three-dimensional fabric is immersed in the impregnating agent for immersion treatment, and then dried; wherein the immersion pressure is 0.4-5 MPa, the immersion time is 12-24 hours; the drying temperature is 60-110° C., and the drying time is 1-3 hours; Specifically, the wetting agent includes any one or more of ethyl acetate, acetone or toluene.
[0023] Specifically, the inert atmosphere includes at least one of nitrogen and argon.
[0024] Specifically, the quartz fiber three-dimensional fabric is prepared by a needle-punching and stitching process.
[0025] The quartz fiber three-dimensional fabric of this embodiment has a thickness of 20-50 mm.
[0026] Specifically, the mass proportion of quartz fiber in the quartz fiber three-dimensional fabric is 35-45%.
[0027] The present invention also provides a low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material obtained based on the low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material preparation method as described in any one of the above.
[0028] The invention provides a low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material preparation method. First, a quartz fiber three-dimensional fabric is treated with liquid borazine. Since the liquid borazine has the characteristic of low viscosity, it can quickly impregnate and fill the gaps in the fiber bundles and between the fiber bundles of the three-dimensional fabric. Due to the high activity and high ceramic rate of the liquid borazine, under the conditions of 80-95°C, 0.2-1.0MPa, and 1-3.5h, the borazine pinched in the gaps between the fiber bundles of the quartz fiber three-dimensional fabric can be quickly foamed into a solid state. There are many quartz fibers with strong surface tension. The borazine between the fiber yarns is converted into a solid with relatively small pores. Under the protection of an inert atmosphere at 800-900°C, the solidified borazine is converted into a boron nitride ceramic, that is, a boron nitride coating is formed on the surface of the quartz fiber to improve the antioxidant and high temperature resistance. The obtained fabric rough is impregnated in silica sol, and then solidified and sintered. The quartz fiber reinforced quartz-based composite material only needs to go through a one-time preparation process, and does not need to go through a cyclic densification process. Its density can reach 1.2-1.6g / cm 3 , meeting the use requirements of low dielectric antenna cover or antenna window for material performance, simple manufacturing process, short preparation cycle, excellent high temperature resistance, low cost and low equipment requirements.
[0029] During the impregnation process of the silica sol of the present invention, the liquid level of the silica sol is lower than the rough fabric, forming a certain height difference. The silica sol can penetrate relatively evenly into the interior of the fabric through the boron nitride pores between the quartz fiber bundles. The impregnation state of the fabric gradually decreases as the temperature increases. The silica sol can be further impregnated into the interior of the fabric through capillary force in the initial stage of curing, and finally the quartz fiber reinforced quartz-based composite material is uniformly dense.
[0030] The quartz fiber three-dimensional fabric of the present invention has a certain thickness of 20-50 mm, and a porous boron nitride matrix is introduced. Through impregnation treatment, it can extend into the deep layer of the quartz fiber three-dimensional fabric. When the composite material is subsequently prepared by impregnating silica sol, a quartz composite material with controllable density can be prepared quickly and at low cost.
[0031] Embodiment 1 A method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material comprises the following steps: 101) Debonding treatment of quartz fiber three-dimensional fabric, specifically, immersing the quartz fiber three-dimensional fabric in a sizing agent for immersion treatment, and then drying it; wherein the immersion pressure is 0.4 MPa, the immersion time is 24 hours, the drying temperature is 80°C, and the drying time is 1 hour; 102) The debinding treated quartz fiber three-dimensional fabric is immersed in liquid borazine, the amount of liquid borazine added is 25% of the weight of the quartz fiber three-dimensional fabric, the temperature is raised to 80°C in an inert atmosphere, the temperature is kept at 0.2 MPa pressure for 3.5 hours, and the fabric rough blank is obtained at 800°C; 103) The rough fabric is immersed in silica sol with a mass concentration of 25%. Under vacuum, the temperature is raised to 55°C and kept warm for 10 hours. After the rough fabric is immersed in the silica sol, the silica sol liquid level is 2 / 3 of the height of the rough fabric; then the temperature is raised to 85°C and kept warm for 10 hours. The silica sol liquid level is 1 / 3 of the height of the rough fabric; the silica sol is removed, the temperature is raised to 125°C and kept warm for 10 hours, then the temperature is raised to 200°C and kept warm for 5 hours, and then sintered at 550°C and kept warm for 3 hours to obtain a low-cost, high-temperature resistant, density-adjustable quartz fiber reinforced quartz-based composite material.
[0032] The infiltrant of this embodiment includes ethyl acetate.
[0033] The inert atmosphere in this embodiment is nitrogen.
[0034] The quartz fiber three-dimensional fabric of this embodiment is prepared by needle-punching and stitching technology.
[0035] The mass proportion of quartz fiber in the quartz fiber three-dimensional fabric of this embodiment is 35%.
[0036] The quartz fiber three-dimensional fabric of this embodiment has a thickness of 50 mm.
[0037] The low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material obtained in this embodiment has a density of 1.2 g / cm 3 The room temperature tensile strength is 46MPa, the tensile strength at 1000℃ is 36MPa, and the dielectric constant is 2.4. It has excellent mechanical properties, high temperature resistance and low dielectric properties.
[0038] Embodiment 2 A method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material comprises the following steps: 201) Quartz fiber three-dimensional fabric debonding treatment, specifically, the quartz fiber three-dimensional fabric is immersed in a sizing agent for immersion treatment, and then dried; wherein the immersion pressure is 0.7 MPa, the immersion time is 12 hours; the drying temperature is 60°C, and the drying time is 2 hours; 202) The debinding treated quartz fiber three-dimensional fabric is immersed in liquid borazine, the amount of liquid borazine added is 25% of the weight of the quartz fiber three-dimensional fabric, the temperature is raised to 85°C in an inert atmosphere, the temperature is kept at 0.6 MPa for 2 hours, and the fabric rough blank is obtained at 850°C; 203) The rough fabric is immersed in silica sol with a mass concentration of 40%. Under vacuum, the temperature is raised to 65°C and kept warm for 10 hours. After the rough fabric is immersed in the silica sol, the silica sol liquid level is 1 / 2 of the height of the rough fabric; then the temperature is raised to 100°C and kept warm for 10 hours. The silica sol liquid level is 1 / 3 of the height of the rough fabric; the silica sol is removed, the temperature is raised to 150°C and kept warm for 10 hours, then the temperature is raised to 220°C and kept warm for 5 hours, and then sintered at 750°C and kept warm for 3 hours to obtain a low-cost, high-temperature resistant, density-adjustable quartz fiber reinforced quartz-based composite material.
[0039] The wetting agent in this embodiment is acetone.
[0040] The inert atmosphere in this embodiment is argon.
[0041] The quartz fiber three-dimensional fabric of this embodiment is prepared by stitching using a needle punching process.
[0042] The mass proportion of quartz fiber in the quartz fiber three-dimensional fabric of this embodiment is 40%.
[0043] The quartz fiber three-dimensional fabric of this embodiment has a thickness of 20 mm.
[0044] The low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material obtained in this embodiment has a density of 1.4 g / cm 3 The room temperature tensile strength is 42MPa, the tensile strength at 1000℃ is 32MPa, and the dielectric constant is 2.6. It has excellent mechanical properties, high temperature resistance and low dielectric properties.
[0045] Embodiment 3 A method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material comprises the following steps: 301) Debonding treatment of quartz fiber three-dimensional fabric, specifically, immersing the quartz fiber three-dimensional fabric in a sizing agent for immersion treatment, and then drying it; wherein the immersion pressure is 1.0 MPa, the immersion time is 12 hours; the drying temperature is 110°C, and the drying time is 3 hours; 302) The debinding treated quartz fiber three-dimensional fabric is immersed in liquid borazine, the amount of liquid borazine added is 20% of the weight of the quartz fiber three-dimensional fabric, the temperature is raised to 95°C in an inert atmosphere, the temperature is kept at 1 MPa pressure for 1 hour, and the fabric is sintered at 900°C to obtain a rough fabric; 303) The rough fabric is immersed in silica sol with a mass concentration of 60%. Under vacuum, the temperature is raised to 60°C and kept warm for 10 hours. After the rough fabric is immersed in the silica sol, the silica sol liquid level is 1 / 2 of the height of the rough fabric; then the temperature is raised to 90°C and kept warm for 10 hours. The silica sol liquid level is 1 / 3 of the height of the rough fabric; the silica sol is removed, the temperature is raised to 140°C and kept warm for 10 hours, and then the temperature is raised to 210°C and kept warm for 5 hours. The rough fabric is sintered at 600°C and kept warm for 3 hours to obtain a low-cost, high-temperature resistant, density-adjustable quartz fiber reinforced quartz-based composite material.
[0046] The wetting agent of this embodiment includes ethyl acetate and toluene, and the mass ratio of ethyl acetate to toluene is 1:1.
[0047] The inert atmosphere in this embodiment is nitrogen.
[0048] The quartz fiber three-dimensional fabric of this embodiment is prepared by needle-punching and stitching technology.
[0049] The mass proportion of quartz fiber in the quartz fiber three-dimensional fabric of this embodiment is 45%.
[0050] The quartz fiber three-dimensional fabric of this embodiment has a thickness of 30 mm.
[0051] The low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material obtained in this embodiment has a density of 1.6 g / cm 3 The room temperature tensile strength is 40MPa, the tensile strength at 1000℃ is 33MPa, and the dielectric constant is 2.8. It has excellent mechanical properties, high temperature resistance and low dielectric properties.
[0052] Embodiment 4 The difference between this embodiment and the first embodiment is that the debinding treated quartz fiber three-dimensional fabric is immersed in liquid borazine, heated to 90°C in an inert atmosphere, kept at a pressure of 0.5 MPa for 2 hours, and sintered at 850°C to obtain a rough fabric.
[0053] The low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material obtained in this embodiment has a density of 1.2 g / cm 3The room temperature tensile strength is 45MPa, the tensile strength at 1000℃ is 33MPa, and the dielectric constant is 2.4. It has excellent mechanical properties, high temperature resistance and low dielectric properties.
[0054] Comparative Example 1 The difference between this comparative example and Example 1 is that there is no 102 treatment step, and the obtained quartz fiber reinforced quartz-based composite material has a density of 1.05 g / cm 3 The room temperature tensile strength is 41MPa, the tensile strength at 1000℃ is 15MPa, the dielectric constant is 2.15, the density of the composite material is relatively low, and the high temperature resistance is poor.
[0055] Compared with Example 1, the comparative example does not use liquid borazine to pre-treat the quartz fiber three-dimensional fabric, but directly uses silica sol for treatment, and the density of the composite material is relatively low, and the high temperature resistance is poor. The boron nitride coating prepared by the quartz fiber three-dimensional fabric under the conditions of rapid curing under certain impregnation temperature and pressure and sintering temperature plays a very important role in the high temperature resistance of the quartz fiber.
[0056] Comparative Example 2 The difference between this comparative example and Example 3 is only in step 103. In this comparative example, the rough fabric is immersed in silica sol, and the temperature is raised to 55°C under vacuum and kept warm for 10 hours. After the rough fabric is immersed in the silica sol, the silica sol liquid level is greater than the height of the rough fabric; the temperature is then raised to 85°C and kept warm for 10 hours, and the silica sol liquid level is greater than the height of the rough fabric; the silica sol is removed, the temperature is raised to 125°C and kept warm for 10 hours, and then the temperature is raised to 200°C and kept warm for 5 hours, and the rough fabric is sintered at 550°C and kept warm for 3 hours to obtain a low-cost, high-temperature resistant, density-adjustable quartz fiber reinforced quartz-based composite material.
[0057] The obtained quartz fiber reinforced quartz matrix composite material has a density of 1.43g / cm 3 The room temperature tensile strength is 39MPa, the tensile strength at 1000℃ is 28MPa, the dielectric constant is 2.62, and the density of the composite material is relatively low.
[0058] In this comparative example, the impregnation effect is poor after all the fabrics are immersed in silica sol at the beginning, and the density of the composite material is relatively low. When the impregnation is started in Example 3, the silica sol liquid level is 1 / 2 of the height of the rough fabric; then the temperature is raised to 90°C and kept warm for 10 hours, and the silica sol liquid level is 1 / 3 of the height of the rough fabric. By using the capillary force, the impregnation effect of the same silica sol can be further improved, and the density of the quartz / quartz composite material is significantly improved.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material, characterized in that: The steps include: Quartz fiber three-dimensional fabric debonding treatment; The debinding treated quartz fiber three-dimensional fabric is immersed in liquid borazine, heated to 80-95° C. in an inert atmosphere, kept warm for 1-3.5 hours at a pressure of 0.2-1.0 MPa, and sintered at 800-900° C. to obtain a rough fabric; The rough fabric is impregnated in silica sol, heated and kept warm under vacuum, and after impregnation, the silica sol is removed, heated and kept warm under vacuum, and sintered to obtain a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material.
2. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 1, characterized in that: The rough fabric is immersed in silica sol, the liquid level of silica sol is 1 / 2-2 / 3 of the height of the rough fabric, the temperature is raised to 55-65°C under vacuum, and the temperature is kept for 10 hours, the liquid level of silica sol is lowered to 1 / 10-1 / 2 of the height of the rough fabric, and the temperature is raised to 85-100°C and the temperature is kept for 10 hours; Remove the silica sol, first raise the temperature to 125-150°C and keep it for 10 hours, then raise the temperature to 200-220°C and keep it for 5 hours, sinter at 500-750°C and keep it for 1-3 hours, and obtain a low-cost, high-temperature resistant, density-adjustable quartz fiber reinforced quartz-based composite material.
3. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 1, characterized in that: The added amount of liquid borazine is 20%-30% of the weight of the quartz fiber three-dimensional fabric.
4. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 1, characterized in that: The mass concentration of silica sol is 25-60%.
5. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 1, characterized in that: Quartz fiber three-dimensional fabric debonding process: The quartz fiber three-dimensional fabric is immersed in the impregnating agent for immersion treatment, and then dried; wherein the immersion pressure is 0.4-5 MPa, the immersion treatment time is 12-24 hours; the drying temperature is 60-110° C., and the drying time is 1-3 hours.
6. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 4, characterized in that: The wetting agent includes any one or more of ethyl acetate, acetone or toluene.
7. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 1, characterized in that: The inert atmosphere includes at least one of nitrogen and argon.
8. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 1, characterized in that: The quartz fiber three-dimensional fabric is prepared by needle-punching and stitching technology.
9. The method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber-reinforced quartz-based composite material according to claim 1, characterized in that: The mass proportion of quartz fiber in quartz fiber three-dimensional fabric is 35-45%.
10. A low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material obtained based on the method for preparing a low-cost, high-temperature-resistant, density-adjustable quartz fiber reinforced quartz-based composite material according to any one of claims 1 to 9.
Citation Information
Patent Citations
A high-temperature resistant silica fiber reinforced silica-based composite material, its preparation method and application
CN108911777B
A high-density fiber-reinforced quartz ceramic composite material and its preparation method
CN113896554B
High temperature resistant broadband wave-transparent ceramic matrix composite and preparation method thereof
CN102093066A
High-temperature-resistant narrow-frequency-band wave-transmitting composite material and preparation method thereof
CN102659413A
BN interface phase containing quartz / quartz composite material and preparation method therefor
CN110511049A